Uji Efektivitas Metarhizium anisopliae Metch. dan Beauveria bassiana Bals. terhadap Ulat Grayak (Spodoptera litura F.) pada Tanaman Kedelai (Glicyne max L.) di Rumah Kassa - Tobing, Sri Sartika L.; Marheni, Marheni; Hasanuddin, Hasanuddin (Jurnal Agroekoteknologi, 2016)
The objective of the research was to study the effectivity of Metarhizium anisopliae Metch. and Beauveria bassiana Bals. against oriental leafworm moth (Spodoptera litura F.) in soybean (Glicyne max L.) was conducted at the screen house Faculty of Agriculture, University of Sumatra Utara, from November 2013 until April 2014, using randomized block design non factorial with 7 treatments control, M. anisopliae 104/ml, 106/ml and 108/ml, B. bassiana 104/ml, 106/ml and 108/ml with three replications. The results showed that the highest percentage of mortality in treatment for M. anisopliae 108/ml with 100%. The highest percentage of larvae become pupae in control with 100%. The highest percentage intensity of larvae on leaves B. bassiana 104/ml and for B. bassiana with 19.67%. The quickest death time was on the second day after application in treatment M. anisopliae.Keywords: Spodoptera litura, Metarhizium anisopliae, Beauveria bassiana, Glicyne max